The Pregnane-X receptor regulates steroid synthesis in mouse Leydig cells - Martinot, Emmanuelle; Holota, Hélène; de Haze, Angélique; Beaudoin, Claude; Volle, David H. (Frontiers in Endocrinology, 2025)
Pregnane X Receptor (PXR, NR1I2) is a ligand-dependent transcription factor belonging to the nuclear receptor superfamily, that can be activated by a wide variety of endogenous and exogenous ligands. It is a major actor of the endo- and xeno-biotic detoxification process. It also regulates biological processes such as lipid metabolism in large number of tissues. Pxr was shown to be expressed in human, mouse, rat and pig testis, however its roles in the regulation of testicular functions have been little explored so far. Our analyses confirmed the presence of Pxr transcripts in the mouse testis, particularly in Leydig cells. To determine the potential involvement of PXR in the regulation of steroidogenesis, experiments were performed on a wild type (MLTC-1WT) and a Pxr knock-down (MLTC-1PxrKD) mouse Leydig cell line (MLTC-1 cells), treated with a PXR agonist (SR-12813) in acute and chronic conditions. A lower testosterone concentration was measured in MLTC-1PxrKD cells compared to wild type cells. Moreover, both acute and chronic stimulation of MLTC-1WT cells with SR-12813 led to a decrease in testosterone concentration, associated with a lower expression of some steroidogenic genes. This negative impact of SR-12813 on Leydig cell steroidogenesis was counteracted by Pxr knock down. Overall, these results support the involvement of PXR in the regulation of testosterone homeostasis in mouse Leydig cells and open new avenues of research into the involvement of this receptor in the deleterious effects of certain endocrine disruptors on the steroidogenic activity of Leydig cells.